On geometric extension of polynomials on Banach spaces - Verkalets, N.B.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2013)
We consider some questions related to Aron-Berner extensions of polynomials on infinitely dimensional complex Banach spaces, using natural extensions of their zeros.